Etiopathogenesis, Frequency and Significance of Anemia in Heart Failure - Ćirić Zdravković, Snežana (Medical Word, 2026)
Anemia and iron deficiency are common comorbidities in patients with heart failure (HF). In patients with HF, the prevalence of anemia and iron deficiency varies depending on the population studied. In the SOLVD study, 22% of patients had a hematocrit ≤39%, and 4% had values below 35%. The incidence of anemia appears to increase with worsening functional class (from 9% for NYHA class to 79% for NYHA class IV). Symptoms of reduced oxygen delivery due to anemia generally occur only in severe anemia, but may also occur with less severely decreased hemoglobin levels in patients with HF. Diagnosis of anemia in patients with HF should include consideration of HF-related etiology as well as other causes.  Suggested initial testing includes: complete blood count, including red blood cell counts, reticulocyte count, and peripheral blood smear evaluation, measurement of iron, C-reactive protein, sedimentation, vitamin B12, and serum folate levels. Iron deficiency should be corrected and the cause investigated. In patients with HF who do not have symptoms attributable to anemia, the use of a restrictive red cell transfusion strategy is suggested. Intravenous administration of iron leads to improvement of symptoms and improvement of prognosis in terms of reduction in the number of hospitalizations. Such benefits were not observed in patients receiving oral iron preparations. The presence of anemia in heart failure is a predictor of poor prognosis and should be diagnosed and adequately treated.
Keywords: anemia; heart failure; iron deficiency